Identification of Student Misconceptions in General Biology Courses using Four Tier Multiple Choice Tests Containing High Order Thinking Skills - Mariana Ade Cahaya; Mimien Henie Irawati Al Muhdhar; Betty Lukiati (Postgraduate, University of Mataram, 2024)
This research aims to identify misconceptions of biology education students in the General Biology course. The method used in this research uses quantitative descriptive. The sample used in this research was Biology education students who had taken General Biology courses consisting of students in semesters 3, 5, and 7. Data collection was carried out using a test in the form of General Biology questions in a four-tier multiple-choice diagnostic format containing high-order thinking skills, totaling 35 questions. The research results showed that the percentage of misconceptions in each class was 43.80% (semester 3), 33.93% (semester 5), and 29.46% (semester 7). The highest percentage of misconception categories among third-semester students was found in the digestive system material (57.78%), fifth-semester students in ecology material (56.67%), and seventh-semester students in ecological material (40.00%). Misconceptions in students could be caused by students not being used to working on this type of question HOTS. To be able to answer correctly, students must be able to analyze and relate the data or information in the question to existing concepts